Retrospective Cohort Analysis of Outpatient Antibiotic Use for Clostridioides difficile-Indicated Agents in British Columbia, from 2000 to 2018 - Ariana Saatchi; Sungeun Kim; Fawziah Marra (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Clostridioides difficile (CDI) is the most common cause of nosocomial diarrheal infections. Historically, metronidazole was the first-line treatment, but guidelines now indicate oral vancomycin and fidaxomicin as primary antibiotics for initial episodes. A provincial stewardship program has operated in British Columbia (BC), since 2005. Since the program's inception, surveillance of antibiotic use has been ongoing. However, this is the first study to review community-acquired CDI-indicated antibiotic use. Moreover, this study offers the first interpretation of fidaxomicin use in BC since its addition to the provincial formulary. Methods. A retrospective cohort analysis included all outpatient dispensations for CDI-related antibiotics from January 1, 2000, to December 31, 2018. Antibiotic dispensations were extracted for metronidazole, vancomycin, and fidaxomicin. Consumption rates were calculated as prescriptions per 1000 population. Rates were examined overall and then stratified by medication, age, and sex. Secondary outcomes of interest included an examination of adherence to provincial special authority criteria; and proportions of outpatient antibiotic use attributable to administrative health records for CDI. Results. The average annual rate of prescribing was 18.5 per 1000 population for all CDI-indicated antibiotics. The rate of prescribing increased (15%) over the 19-year study period, from 17.2 to 19.8 dispensations per 1000 population. Metronidazole accounted for the most antibiotics dispensed in every study year; however, by 2018 it demonstrated the most modest increase in use (15%). In comparison, fidaxomicin increased by 226% by 2018. Vancomycin had the highest percentage increase (621%), with the greatest change occurring from 2014 to 2015, correlating to the dissemination of new clinical practice guidelines. Conclusion. This is the first study to evaluate outpatient prescribing for CDI-indicated antibiotics, and one of the few studies to examine fidaxomicin since its introduction to Canadian formularies. Although causation cannot be inferred from study results, oral vancomycin, and fidaxomicin use has increased in line with, or in advance-of guidelines.